Regional Issue Identification and Assessment program (RIIA). Environmental impacts and issues of the EIA MID-MID scenario: Federal Region I (New England) - Brainard, J.; Munson, J.S. (Brookhaven National Lab., Upton, NY (USA). National Center for Analysis of Energy Systems, 1979)
The impacts described here for 1985 and 1990 are based on a national energy projection which assumes medium energy demand and fuel supply through 1990 but does not incorporate the policies of the National Energy Act (NEA). This scenario, referred to as the Projection Series C or the TRENDLONG MID-MID scenario, is one of six possible energy futures developed by the DOE Energy Information Administration for the Department's 1977 Annual Report to Congress. It was chosen as representative of the official DOE national energy projections when this project was initiated, prior to the passage of the National Energy Act. Since the RIIA program is part of an ongoing review of the regional impact of energy policies, the next phase will examine the National Energy Act (NEA) and initiatives suggested by the President's second National Energy Plan. However, since coal utilization increases under the NEA, in general, impacts identified in the TRENDLONG Series C Scenario should provide a framework for the discussion of impacts by NEA. The environmental impacts discussed in this volume are for Federal Region I (Maine, Vermont, New Hampshire, Massachusetts, Rhode Island, and Connecticut). However, there are nine companion volumes, one for each of the other Federal Regions.